Water holding capacity and microstructure of sturgeon (Acipenser gueldenstaedti) fillets as affected by low temperature vacuum heating. Issue 1 (1st January 2021) - Wei, Jianling; Chen, Yuewen; Dong, Xiuping; He, Fanyu; Shi, Yugang; Chai, Tingting
ABSTRACT: This study was aimed to investigate the effect of low-temperature vacuum heating (LTVH; versus the traditional thermal method– TC - 100°C boiling water) on water content/distributions, microstructure, and tenderness of sturgeon fillets. Although all fillets were well done, those fillets heated at lower temperature/time showed higher moisture content ( P < .05). Furthermore, microstructure by paraffin section and shear force results also indicated LTVH70-30 (LTVH method; 70°C, 30 min) shown the most similar to TC fillets, the less firm and less juicy. Oppositely, LTVH60-15/30 (LTVH method, 60°C, 15/30 min) showed the best tenderness/juiciness among all fillets. Therefore, the LTVH method is agood alternative to the TC for fish processing in the catering industry, with tenderness/juiciness gains. Graphical abstract of sturgeon fillets by low temperature vacuum heating GA: uf0001